(untitled) (Experimental biology, 2015)
The article presents the results of studying the influence of the nutrient medium composition Fitzgerald, Elenkyn, Bold to the growth of strains Oocystis rhomboideus, Scenedesmus obliquus, Dictyochlorella globosa. It is established that for the rapid accumulation of biomass of green microalgae, paired with a high production of total lipids to use the Fitzgerald nutrient medium for Scenodesmus obliquus, Oocystis rhomboideus and/or Bold nutrient medium Dictyochlorella globosa.